المشكلات التدريسية التي يعاني منها الطالب في فرع العلوم الانسانية في الكلية التربوية المفتوحة / مركز ذي قار - خلف جاسم كريم آل كريم, فارس (Journal of College of Education, 2020)
The aim this the research for knowing the problems of studies which of suffer from the student in branch sciences humanity in college of education opening-center Thi Qar for the study year(2016-2017).consist the sample research from (100)pupil choice the researcher part them(92)pupil (male and female)and accommodate questionnaire organic which ensure the research from validity and show on group from adept and specialists in curriculum and methods study and science psychology education and measurement and evaluation and veliability      account by method(test-retest)and account degree (0,87)and after that the application the research questionnaire on sample of reason original and which consist (92)pupil(male and female)and  the researcher treat   with this data statistic and clarity the results to the found problems studies which suffer of studying in   branch science humanity in collage education opening –Thar qar.